Dual-targeting for brain-specific drug delivery: synthesis and biological evaluation. (1st January 2018) - Yue, Qiming; Peng, Yao; Zhao, Yi; Lu, Runxin; Fu, Qiuyi; Chen, Yang; Yang, Yang; Hai, Li; Guo, Li; Wu, Yong
Abstract: Ibuprofen is one of the most potent non-steroid anti-inflammatory drugs (NSAIDs) and plays an important role in the treatment of neurodegenerative diseases. However, its poor brain penetration and serious side effects at therapeutic doses, has hindered its further application. Thus, it is of great interest to develop a carrier-mediated transporter (CMT) system that is capable of more efficiently delivering ibuprofen into the brain at smaller doses to treat neurodegenerative diseases. In this study, a dual-mediated ibuprofen prodrug modified by glucose (Glu) and vitamin C (Vc) for central nervous system (CNS) drug delivery was designed and synthesized in order to effectively deliver ibuprofen to brain. Ibuprofen could be released from the prepared prodrugs when incubated with various buffers, mice plasma and brain homogenate. Also, the prodrug showed superior neuroprotective effect in vitro and in vivo than ibuprofen. Our results suggest that chemical modification of therapeutics with warheads of glucose and Vc represents a promising and efficient strategy for the development of brain-targeting prodrugs by utilizing the endogenous transportation mechanism of the warheads.